2018
DOI: 10.1186/s40550-018-0065-2
|View full text |Cite
|
Sign up to set email alerts
|

Microbial quality of ready-to-eat vegetable salads vended in the central business district of Tamale, Ghana

Abstract: Background: Food safety problems still persist across the globe and remain a challenge to the general public and government. The study determined the microbiological quality of pre-cut vegetable salads sold in the Central Business District (CBD) of Tamale. Results: A total of thirty (30) salad samples were purchased from four zones of the District and transported to the Spanish Laboratory of the University for Development Studies, Ghana for analysis. Standard microbiological methods that are in accordance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 16 publications
(21 reference statements)
5
59
5
2
Order By: Relevance
“…Consumption of vegetables containing resistant Salmonella and Escherichia coli isolates is a threat to public health and needs to be given attention especially in countries where such phenomena is possible and rampant. Contamination of ready-to-eat vegetable salads by microbes in the Tamale metropolis has been reported (Abakari et al 2018). Also, contamination of mixed vegetables by total aerobic bacteria and Staphylococcus aureus but not Salmonella species in the Kumasi metropolis has been reported (Amoah 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of vegetables containing resistant Salmonella and Escherichia coli isolates is a threat to public health and needs to be given attention especially in countries where such phenomena is possible and rampant. Contamination of ready-to-eat vegetable salads by microbes in the Tamale metropolis has been reported (Abakari et al 2018). Also, contamination of mixed vegetables by total aerobic bacteria and Staphylococcus aureus but not Salmonella species in the Kumasi metropolis has been reported (Amoah 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Low contamination rate in raw vegetables have previously been reported in the Czech Republic (0.3%) by Vojkovska et al (2017) and in Italy (0.75%) by De Giusti et al (2010). However, Abakari et al (2018) showed 73.3% contamination rate of Salmonella spp. in REVS samples vended in Ghana which was too higher than what we found in our research.…”
Section: Discussionmentioning
confidence: 75%
“…Such differences can be due to variation of sanitary conditions during cultivation, harvesting, packaging, distribution, and preparation of the vegetables in the studied regions. It has shown that different hygienic practices may affect the prevalence rate of bacterial contamination in the vegetable samples such as food vendors and also the sources of cultivation (Abakari et al, 2018;Gurler et al, 2015;León et al, 2013). However, we found no significant relation with the Salmonella contamination rate and the area from which our vegetables were obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In New Zealand, S. aureus was counted in lettuce from various production systems with feeds ranging from 10 2 to 10 3 CFU/g (Wadamori et al, 2016). Salmonella sp (0 to 10 4 ) loads have been found recently in urban lettuce production in Ghana (Abakari et al, 2018). The high contamination of lettuce is also due to soil that has been heavily contaminated by the presence of dumpsites in the area, surroundings in addition to wastewater.…”
Section: Discussionmentioning
confidence: 99%